Training to Proficiency in the WHO Hand Hygiene Technique. (August 2019) - Lacey, Gerard; Showstark, Mary; Van Rhee, James
Objectives: Hand hygiene is critical to patient safety, but low performance in terms of the quantity and quality of hand hygiene is often reported. Training-to-proficiency is common for other clinical skills, but no proficiency-based training program for hand hygiene has been reported in the literature. This study developed a proficiency-based training program to improve hand hygiene quality in line with World Health Organization (WHO) guidelines and assessed the amount of training required to reach proficiency. The training was delivered as part of a 5-day induction for students on the Physician Assistant online program. Methods: A total of 42 students used a simulator to objectively measure hand hygiene technique over a 5-day period. Proficiency was achieved when students demonstrated all 6 steps of the WHO technique in less than 42 seconds. The students also completed a postintervention questionnaire. Results: The average training episode lasted 2.5 minutes and consisted of 4.5 hand hygiene exercises. The average student completed 5 training episodes (1 per day) taking a total of 17 minutes. A total of 40% (17) of the students achieved proficiency within the 5 days. Proficiency was strongly correlated with the number of training exercises completed ( r = 0.79, P < .001) and the total time spent training ( r = 0.75, P < .001). Linear regression predicted that the 32 hand hygiene exercises or a total of 23-minute training were required to achieve proficiency. Conclusions: This is the first study to develop a train-to-proficiency program for hand hygiene quality and estimate the amount of training required. Given the importance of hand hygiene quality to preventing health care–associated infections (HAIs), medical education programs should consider using proficiency-based training in hand hygiene technique.